Analisys of Hull Shape Art, Speed, Resistance, Power Using Holtrop Method On A Vessel With DWT 12,335 Ton - Caecielia, Indira Joan; Tuharea, Natasha Dewanti (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2022)
A general cargo vessel carries various kinds of cargo in the form of goods. The goods transported are usually packaged goods. General cargo vessels are equipped with cargo cranes to facilitate the loading and unloading of cargo. This study aims to determine the relation between speed, resistance, and power using the Holtrop method on vessels with a DWT of 12,335 Tons. The ship was modelled using shipping software, and then validated the results with Holtrop mathematical calculations. Holtrop method for calculating tankers, general cargo, fishing vessels, tugs, passengers, containers, and frigates By using the main dimensions of the ship with Length Over All (LOA) 129.8 m, Length Between Perpendicular (LBP) 110 m, Length On Load Waterline (LWL) 112.75 m, Breadth (B) 18 m. height (H) 9 m, Draft (H) 7.2 m, Speed (V) 12.5 Knots. Tests were carried out on Maxsurf Software by calculating resistance and obtaining a graph that displays the relationship between power and speed and resistance and speed.